2017
DOI: 10.3201/eid2302.161374
|View full text |Cite
|
Sign up to set email alerts
|

Swine Influenza Virus (H1N2) Characterization and Transmission in Ferrets, Chile

Abstract: Phylogenetic analysis of the influenza hemagglutinin gene (HA) has suggested that commercial pigs in Chile harbor unique human seasonal H1-like influenza viruses, but further information, including characterization of these viruses, was unavailable. We isolated influenza virus (H1N2) from a swine in a backyard production farm in Central Chile and demonstrated that the HA gene was identical to that in a previous report. Its HA and neuraminidase genes were most similar to human H1 and N2 viruses from the early 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
6
14
0
Order By: Relevance
“…In contrast, an H1N2 strain from South Korea that had the pH1N1 internal gene cassette was found to infect directly inoculated and contact ferrets and also be transmitted at a lower efficiency, to ferrets indirectly exposed to airborne respiratory droplets (42). In a similar fashion, an H1N2 reassortant strain from Chile containing the pH1N1 internal gene cassette was also transmitted between ferrets by direct and indirect routes (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an H1N2 strain from South Korea that had the pH1N1 internal gene cassette was found to infect directly inoculated and contact ferrets and also be transmitted at a lower efficiency, to ferrets indirectly exposed to airborne respiratory droplets (42). In a similar fashion, an H1N2 reassortant strain from Chile containing the pH1N1 internal gene cassette was also transmitted between ferrets by direct and indirect routes (19).…”
Section: Discussionmentioning
confidence: 99%
“…One such H1H2 reassortant gave rise to a human clinical case of influenza in a worker on a swine farm (18). A reassortant H1N2 virus strain was also isolated from pigs in Chile; this virus incorporated human-origin HA and NA gene segments prevalent in the 1990s and the pH1N1 internal gene cassette (19). Human infection with swine-origin H1N2 viruses (H1N2v infection) has been reported in the United States, most notable being 3 human influenza cases linked to infection with a related co-circulating H1N2 swine IAV virus incorporating a pH1N1-origin M gene segment (20).…”
Section: Interspecies Transmission Of Reassortant Swine Influenza a Vmentioning
confidence: 99%
“…Concerningly, Bravo-Vasquez et al (2016) identified the presence of influenza A virus in BPS in central Chile, with seroprevalence ranging from 42 to 60% at BPS level while Jimenez-Bluhm et al (2018a) found that influenza virus positivity by real-time RT-PCR (qRTPCR) ranged from 0% to 45.8% at the farm level. Furthermore, influenza virus has been isolated in pigs in BPS in Chile; results that are very interesting as the isolated virus was a swine-human reassortant that could represent a potential threat to public health (Bravo-Vasquez et al, 2017). Hence, not only the productive systems may be in risk, but also public health.…”
Section: Discussionmentioning
confidence: 99%
“…The HA segments of these Chilean IAVs were likely introduced into swine from humans in the late 1980s and early 1990s 24 . Hence, these viruses evolved in the swine population for over two decades, and now they are genetically distant from other human IAVs described worldwide [24][25][26] . Moreover, these Chilean strains have unique glycosylation site patterns, which were not detected in human IAV strains 20 .…”
Section: Discussionmentioning
confidence: 99%